Aplicación de técnicas geológicas al estudio de fragmentos de cerámica Halaf de la Cuenca del Río Balikh (Siria) - Pozo Rodríguez, Manuel; Casas de Pedro, José Antonio; Moreno Gutiérrez, Ángel; Martín Rubí, J. A. (ISIMU, 2016)
The mineralogicai, petrographic and geochemical study of Halaf sherds (6.000-5000 b.C) from ten sampling points along Balikh river basin (Syria) has been done. On the basis of colour red, brown and green ceramics have been differentiated. Petrography shows vacuolar texture and low temper content (<5%) in green samples but clastic texture and higher temper content (10-30%) in brown and red sherds. From a mineralogical point of view three assemblages have been observed : Assemblage 1. : Calcite > quartz - feldspar > (phyilosilicates - hematites - gehlenite - hornblende) Assemblage 2. : Quartz - feldspar > augite - gehlenite - calcite > (phyliosilicates - hematites - dolomite) Assemblage 3. : Quartz - feldspar > caicite - gehlenite > (augite - phyliosilicates - hematites - dolomite) Samples with high gehlenite or calcite content let os to establish a firing range between 700-900 iC, being remarkable the relation between firing temperatures and sherd colour: red (R2) < red (R1 & R3) < brown (M) <green (V)). A correlation between sherd composition (mineralogy and geochemistry) and sampling points have not been observed. Results suggest intensive pottery trading activity in the Balikh basin during the Halaf Period.